Relationship between good governance determinants for healthcare administration and health outcomes in Multan district public hospitals, Pakistan - Dawood, Nawaz (2021)
Existing literatures reveal that there was a gap in the empirical knowledge on the determinants of good governance in healthcare administration among public hospitals. Good governance is a key factor in the development of the healthcare sector. Therefore, the main objective of this study is to examine the relationship between determinants of good governance in healthcare administration and health outcomes among public hospitals in Pakistan. This study provides a detailed investigation into the relationship between determinants of good governance and health outcomes by proposing a significant relationship between determinants of good governance (accountability, equity, responsiveness, and transparency) and health outcomes. The research framework of this study was developed based on the theory of good governance in the context of healthcare. Survey questionnaires were distributed among the employees (doctors, nurses, administrative staffs) and patients of public hospitals in Multan district, Pakistan by using the proportionate sampling method. The collected data were analyzed using SPSS and SMART PLS 3.0 applications and this study used structural equation modeling (SEM) to test the relationship among the variables. After the preliminary tests and assumptions testing, 485 surveys (238 from employees and 247 from patients) were found to be valid for further analysis. The hypothesis testing indicates that equity, responsiveness, and transparency appear to have a significant relationship with health outcomes, while accountability has an insignificant influence on health outcomes from both the employees and patients’ perspectives. This study contributes towards the good governance practice in the healthcare sector where it identify the key determinants of good governance, and at the same time integrates the governance theory in the context of healthcare. It also offers contextual, methodological, practical as well as theoretical contributions and implications for the healthcare administrators, governing bodies, policy-makers, and stakeholders of public as well as private hospitals, who are interested in improving the good governance practice in healthcare sector. Finally, the limitation of the study and directions for future research are also discussed.